2018
DOI: 10.1155/2018/4646852
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Control and Asthma Medication Use among Swedish Elite Endurance Athletes

Abstract: Background Asthma is common in elite athletes. In this study, we examined the use of asthma medication and asthma control in endurance athletes in Sweden and compared the findings with those in a reference group of patients with asthma. Methods The Asthma Control Test (ACT) and a questionnaire on asthma, respiratory symptoms, and medication use were posted to endurance athletes (n=711) and the reference group of patients with asthma (n=1026). Four hundred and sixty-nine athletes (66%) responded, of whom 141 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Asthma control in skiers has been recently studied in two Swedish studies. 5,6 The first study included elite crosscountry skiers and orienteers and found that 82% of the athletes had well-controlled asthma, 6 but the results were not divided based on the sport. Among adolescent crosscountry skiers aged 12-15 years (n = 20), the median Asthma Control Test (ACT) score was 21, suggesting wellcontrolled asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma control in skiers has been recently studied in two Swedish studies. 5,6 The first study included elite crosscountry skiers and orienteers and found that 82% of the athletes had well-controlled asthma, 6 but the results were not divided based on the sport. Among adolescent crosscountry skiers aged 12-15 years (n = 20), the median Asthma Control Test (ACT) score was 21, suggesting wellcontrolled asthma.…”
Section: Introductionmentioning
confidence: 99%
“…We also find it reasonable that not all athletes with current asthma used HMEs. A large proportion of Swedish skiers have well‐controlled asthma 19 and thus little need of HMEs. Also, some of the skiers in the present study did not experience relief by HMEs or felt HMEs hindered their training.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 191 responding skiers, 167 (87%) were cross-country skiers, and the remaining 24 (13%) were biathletes. The respondents had a mean (range) age of 17 (15)(16)(17)(18)(19) years; 101 (53%) were women. A majority of the skiers (55%) trained 10-13 h/wk, while six skiers trained <6 h/wk, and three skiers trained ≥18 h/wk.…”
Section: Study Populationmentioning
confidence: 99%
“…On the contrary, an increased use of SABA/LABA is an indication, for the treating physician, to introduce or increase the use of controller medication, such as ICS, and thus reduced the need for SABA. Elite cross-country skiers with asthma do not appear to use more SABA/LABA than a reference group of patients with asthma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%